Topics in economics of higher education: Choices and returns - Anne Toft Hansen (University of Copenhagen, Department of Economics, 2019)
In standard economic theory, education is an investment, and you choose to invest if the future returns are higher than the costs of investment. The future returns are often thought of in terms of monetary returns but education has also shown to have an effect on several nonpecuniary factors. In recent years, the literature has found an association between education and factors like fertility 5, crime, health, success in the marriage market, and happiness. 6 Additionally, the literature on the choice of education, shows that the prospects of different nonpecuniary factors are more important than pecuniary for prospective students. 7 This dissertation adds to the literature with three self-contained chapters dealing with different aspects of choice and returns to higher education. Chapter 1 examines gender differences in the choice of higher education, chapter 2 investigates the role of university location on where graduates end up living and working, and chapter 3 examines the signaling value of the GPAs of university graduates in their first five years on the labor market.
Keywords: 330